2000
DOI: 10.1038/35018568
|View full text |Cite
|
Sign up to set email alerts
|

Transformation from temporal to rate coding in a somatosensory thalamocortical pathway

Abstract: The anatomical connections from the whiskers to the rodent somatosensory (barrel) cortex form two parallel (lemniscal and paralemniscal) pathways. It is unclear whether the paralemniscal pathway is directly involved in tactile processing, because paralemniscal neuronal responses show poor spatial resolution, labile latencies and strong dependence on cortical feedback. Here we show that the paralemniscal system can transform temporally encoded vibrissal information into a rate code. We recorded the representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
327
5
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(366 citation statements)
references
References 27 publications
33
327
5
1
Order By: Relevance
“…Repetitive stimulation of individual whiskers is characterized by a decrease in responsiveness in the neocortex. S1 neurons are generally ooly responsive to low frequency whiske~stimulation and often respond exclusively to the tirst stimulus presented (Ahissar, 2000;Simons, 1978;Swadlow, 1989). Field potential responses evoked in SI by whisker stimulation depress at frequencies above 5 Hz (Sheth et al, 1998).…”
Section: Short-term Plasticity Ofsensory Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Repetitive stimulation of individual whiskers is characterized by a decrease in responsiveness in the neocortex. S1 neurons are generally ooly responsive to low frequency whiske~stimulation and often respond exclusively to the tirst stimulus presented (Ahissar, 2000;Simons, 1978;Swadlow, 1989). Field potential responses evoked in SI by whisker stimulation depress at frequencies above 5 Hz (Sheth et al, 1998).…”
Section: Short-term Plasticity Ofsensory Responsesmentioning
confidence: 99%
“…In fact, bath VPM and Pom neurons depress when stimulated at frequencies above 5 Hz (Ahissar, 2000;Diamond et al, 1992). Depression ofVPM neurons to repetitive whisker stimulation will have a great impact on cortical sensory suppression because they carry the input producing the primary response in Si.…”
Section: Short-term Plasticity Ofsensory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such POm TCAs also terminate in the dysgranular cortex that separates major body parts within the somatosensory cortex. This pathway—the so-called paralemniscal pathway—conveys signals related to vibrissal movement (Ahissar et al, 2000; Yu et al, 2006). Thus, in rats the two thalamic streams form largely non-overlapping, complementary patterns of terminations in and outside of layer IV, thereby establishing semi-independent circuits for tactile information processing (Koralek et al, 1988; Chmielowska et al, 1989; Lu and Lin, 1993; Kim and Ebner, 1999; Ahissar et al, 2001; Bureau et al, 2006).…”
mentioning
confidence: 99%
“…Thus, Yang and colleagues (67) successfully performed functional MRI of the barrel cortex at stimulation frequencies of 8 Hz. Moreover, it has been shown that different frequencies may activate different parts of the same somatosensory circuit (95) and reveal the mutual interaction between different parts of the circuit.…”
Section: Fmri Applications Fmri Studies Of Somatosensory Neuronal Cirmentioning
confidence: 99%